Clinical outcomes of exercise-induced pulmonary hypertension in subjects with preserved left ventricular ejection fraction: implication of an increase in left ventricular filling pressure during exercise. Issue 17 (7th June 2011) - Shim, Chi Young; Kim, Sung-Ai; Choi, Donghoon; Yang, Woo-In; Kim, Jin-Mi; Moon, Sun-Ha; Lee, Hyun-Jin; Park, Sungha; Choi, Eui-Young; Chung, Namsik; Ha, Jong-Won
Abstract : Objective: To investigate clinical outcomes of exercise-induced pulmonary hypertension (PH) and implications of an increase in left ventricular (LV) filling pressure during exercise in subjects with preserved LV ejection fraction. Design: Longitudinal follow-up study. Setting: Subjects who were referred for diastolic stress echocardiography. Patients and methods: The ratio of transmitral and annular velocities (E/Ea) and pulmonary artery systolic pressure (PASP) at rest and during exercise were measured in 498 subjects (57±11 years; 201 male). Exercise-induced PH was defined as present if PASP ≥50 mm Hg at 50 W of exercise, and an increase in LV filling pressure during exercise was present if E/Ea ≥15 at 50 W. Main outcome measures: A combination of major cardiovascular events and any cause of death. Results: During a median follow-up of 41 months, there were 14 hospitalisations and four deaths. Subjects with exercise-induced PH had significantly worse clinical outcomes than those without (p=0.014). Subjects with exercise-induced PH associated with an increase in E/Ea during exercise had significantly worse outcomes than other groups (p<0.001). However, prognosis was similar between subjects with exercise-induced PH without an increase in E/Ea and those without exercise-induced PH. In subjects with exercise-induced PH, E/Ea at 50 W was an independent predictor of adverse outcomes (HR 1.37; 95% CI 1.02 to 1.83; p=0.036). Conclusions: Exercise-induced PH provides prognostic information in subjects with preserved LV ejection fraction. The excess risk of exercise-induced PH is restricted to subjects with an increase in estimated LV filling pressure during exercise.